Optimal observability in a linear income tax - Joel Slemrod; Christian Traxler (Max Planck Institute for Research on Collective Goods, 2010)
We study the optimal observability of the tax base within the standard linear income tax problem, where observability is determined by the government's investment into the accurate measurement of the tax base. We characterize the optimal level of observability and derive a new expression for the optimal progressivity, which in addition to the standard equity efficiency trade-off accounts for the limited accuracy of an income tax system.
Keywords: H21; H11; D8; 330; optimal linear income taxation; observability; tax enforcement